Seminal Interleukin-6 and Serum Prostate-specific Antigen as Possible Predictive Biomarkers in Asymptomatic Inflammatory Prostatitis - Korrovits, Paul; Ausmees, Kristo; Mändar, Reet; Punab, Margus (Urology (Ridgewood, N.J.), 2011)
To determine the possible predictive values of seminal interleukin-6 (IL-6) and serum prostate-specific antigen (PSA), as well as their combined values, in differentiating between subjects with or without asymptomatic inflammatory prostatitis. The study group consisted of 490 men (mean age 18.9 ± 1.8 years, range 16-25). Cytologic examination of all ejaculates (using Bryan-Leishman-stained slides) and clinical examination for possible pathologic findings in the genital region were performed. The subjects with any clinical symptoms of inflammation were excluded. The levels of PSA in the blood serum and IL-6 in the seminal plasma were also determined. The IL-6 and PSA levels for different leukocytospermia status were statistically compared, and receiver operating characteristic curves were designed to determine the sensitivity versus specificity and the positive and negative predictive values of IL-6 and PSA levels against different thresholds of leukocytospermia (0.2, 0.5, and >1.0 × 10 6 leukocytes/mL). The levels of both IL-6 in the seminal plasma and PSA in the blood serum were significantly greater in National Institutes of Health prostatitis IV than in the controls. The receiver operating characteristic curves for seminal IL-6 and serum PSA showed high negative prognostic values for all 3 leukocytospermic subgroups, and positive prognostic values were seen only with IL-6 in the lower leukocytospermic range. Both seminal IL-6 and serum PSA are excellent negative predictive markers for asymptomatic inflammatory prostatitis in young men, although positive predictive values of these biomarkers remain less indicative in this age group.